The impact of atmospheric teleconnections on the coastal aquifers of Ria Formosa (Algarve, Portugal) - C. Neves, Maria (2020)
Fluctuations in groundwater level in the Ria Formosa coastal aquifers, southern Portugal, owe 80% of the variability to climate-induced oscillations. Wavelet coherences computed between hydraulic heads and the North Atlantic Oscillation (NAO) and East Atlantic (EA) atmospheric teleconnections show nonstationary and spatially varying relationships. The NAO is the most important teleconnection and the main driver of long-term variability, inducing cycle periods of 6-10 years. The NAO fingerprint is ubiquitous and it accounts for nearly 50% of the total variance of groundwater levels. The influence of EA emerges coupled to NAO and is mainly associated with oscillations in the 2-4-year band. These cycles contribute to less than 5% of the variance in groundwater levels and are more evident further from the coast, in the northern part of the system near the main recharge area. Inversely, the power of the annual cycle increases towards the shoreline. The weight of the annual cycle (related to direct recharge) is greatest in the Campina de Faro aquifer, where it is responsible for 20-50% of the variance of piezometric levels. There, signals linked to atmospheric teleconnections (related to regional recharge) are low-pass filtered and have periods >8 years. This behavior (lack of power in the 2-8-year band) emphasizes the vulnerability of coastal groundwater levels to multi-year droughts, particularly in the already stressed Quinta do Lago region, where hydraulic heads are persistently below sea level.